Successful Kidney Re-Transplantation of a Transplanted Kidney 9 Years after the First Transplant. (July 2018) - Ghinea, Ronen; Nesher, Eviatar; Aizner, Sigal; Gurevich, Michael; Mehjibovsky, Vadym; Tennak, Vladimir; Mor, Eytan
Abstract : Transfer of a transplanted organ to a new recipient although rare may be a useful source of organs for transplant. Few cases have been reported in the literature where a transplanted kidney was used again in an interval of 8 weeks to 6 years between the first and the second transplant. In here we report a re-transplantation of a transplanted kidney 9 years after the first transplant. Case Report: The patient was a 55 y/o with polycystic kidney disease who in 2007 underwent kidney transplantation elsewhere. She had a known history of intracranial aneurism for which she was treated with embolization. Her renal function throughout the follow-up was stable with Cr. levels of 0.6-0.9mg/dl under triple immunosuppressive therapy with tacrolimus, MMF and steroids. Nine years after transplant the patient was admitted to the ICU, in coma (GCS-3) due to intra-cranial bleeding and declared brain dead 2 days after admission. The family agreed to direct donation of the kidney to the patient's 51 y/o brother with PCKD who was 7 years on dialysis. The kidney was harvested following perfusion of the infra-renal aorta with UW and immediately transplanted in the brother using the regular technique of vascular (end-to-side to the external iliac vessels) and ureteral anastomosis (Lich-Gregoir). Follow-up: The post-transplant course was uneventful with a drop in creatinine levels to 1.16mg/dl at discharge and. At 17 months after transplant Cr. level is 1.29mg/dl with no evidence of proteinuria. Conclusion: Re-transplantation of a transplanted kidney is possible as long as the graft function is stable even after a long interval of 9 years after the first transplant.